2016
DOI: 10.1111/cge.12832
|View full text |Cite
|
Sign up to set email alerts
|

CLOVES syndrome: review of a PIK3CA‐related overgrowth spectrum (PROS)

Abstract: Overgrowth syndromes are characterized by global or localized disproportionate growth associated with other anomalies, including vascular malformations and neurological and/or visceral disorders. CLOVES (Congenital Lipomatous asymmetric Overgrowth of the trunk with lymphatic, capillary, venous, and combined-type Vascular malformations, Epidermal naevi, Scoliosis/Skeletal and spinal anomalies) is an overgrowth syndrome caused by mosaic activating mutation in gene PIK3CA, which gives rise to abnormal PI3K-AKT-mT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
101
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(101 citation statements)
references
References 46 publications
(66 reference statements)
0
101
0
Order By: Relevance
“…We did not find any of the common PIK3CA mutations in the KLA cells that have been found in vascular anomalies associated with tissue overgrowth including Klippel–Trenaunay syndrome (KTS) and congenital lipomatous overgrowth vascular malformations epidermal nevi and scoliosis/skeletal/spinal anomalies (CLOVES) . In the Glaser study, whole‐exome sequencing of KLA‐derived cells identified a potential pathogenic variant in one KLA patient (which is patient 1607 in our study), a 3‐base pair deletion resulting in loss of Serine 1043 in tuberous sclerosis complex 1 (TSC1).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…We did not find any of the common PIK3CA mutations in the KLA cells that have been found in vascular anomalies associated with tissue overgrowth including Klippel–Trenaunay syndrome (KTS) and congenital lipomatous overgrowth vascular malformations epidermal nevi and scoliosis/skeletal/spinal anomalies (CLOVES) . In the Glaser study, whole‐exome sequencing of KLA‐derived cells identified a potential pathogenic variant in one KLA patient (which is patient 1607 in our study), a 3‐base pair deletion resulting in loss of Serine 1043 in tuberous sclerosis complex 1 (TSC1).…”
Section: Discussionmentioning
confidence: 59%
“…Our kinase array study and verification with Western blot analysis showed high AKT activation as well as MAPK. Hyperactive PI3K–AKT–mTOR signaling has also been found in a number of vascular malformations …”
Section: Discussionmentioning
confidence: 99%
“…Klippel-Trenaunay syndrome (progressive growth of the lower limb with cutaneous capillary malformations and deep vascular malformations), and upper limb MO - hypoplasia IF are also included in this group. All of these disorders are associated with PIK3CA somatic mutations[1, 12, 18, 2225] and the current report…”
Section: Discussionmentioning
confidence: 82%
“…602501) and CLOVES (congenital lipomatous asymmetrical overgrowth of the trunk with lymphatic, capillary, venous and combined‐type vascular malformations, epidermal nevi, scoliosis/skeletal and spinal anomalies; OMIM no. 612918) syndrome …”
Section: Discussionmentioning
confidence: 99%